Once a soldier - Putney, Mary Jo (Putney, Mary Jo. Rogues redeemed, 2016)
As heir to a title and great wealth, Will Masterson should have stayed home and tended his responsibilities. Instead he went to war. Now, after perilous years fighting the French, he intends his current mission to be his last. But all his plans are forgotten when he arrives in the small mountain stronghold of San Gabriel and meets her. Knowing herself to be too tall, strong, and unconventional to appeal to a man, Athena Markham has always gloried in her independence. But for the first time in her life, she finds a man who might be her match. Two of a kind, too brave for their own good, Athena and Will vow to do whatever it takes to vanquish San Gabriel's enemies. For neither will back down from death, and only together can they find happiness and a love deeper than any they'd dared imagine.